2018
DOI: 10.4143/crt.2016.446
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Opinions Related to End-of-Life Discussion: From Oncologists' and Resident Physicians' Perspectives

Abstract: PurposeThe aims of this study were to explore how oncologists and resident physicians practice end-of-life (EOL) discussions and to solicit their opinions on EOL discussions as a means to improve the quality of EOL care.Materials and MethodsA survey questionnaire was developed to explore the experiences and opinions about EOL discussions among oncologists and residents. Descriptive statistics, the t test, and the chisquare test were performed for the analyses.ResultsA total of 147 oncologists and 229 residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Training alone, according to physician respondents, is not sufficient. As observed in other studies, conversations were much more likely to occur when the practice or healthcare system has a formal system in place for assessing patients' end‐of‐life wishes and goals of care, yet fewer than one‐third of physicians responding had such a system in place. This suggests that policymakers should consider additional ways beyond payment to stimulate inclusion of ACP in the practice and health system infrastructure.…”
Section: Discussionsupporting
confidence: 54%
“…Training alone, according to physician respondents, is not sufficient. As observed in other studies, conversations were much more likely to occur when the practice or healthcare system has a formal system in place for assessing patients' end‐of‐life wishes and goals of care, yet fewer than one‐third of physicians responding had such a system in place. This suggests that policymakers should consider additional ways beyond payment to stimulate inclusion of ACP in the practice and health system infrastructure.…”
Section: Discussionsupporting
confidence: 54%
“…An earlier study in the United States reported that parental factors (unrealistic expectation, insufficient understanding of prognosis, and lack of readiness) are the most prevalent barriers to ACP [8]. Further, Korean oncologists (internal medicine) also opined that familial factors (reluctance, hope, and conflict) and unclear prognosis are more frequent barriers than a lack of systemic support or scarcity of knowledge, which correspond to the results of the current study [22]. According to the result, only 20 participants (22.4%) received appropriate education in this matter (Table 1) and 55.0% were lacking in confidence regarding pediatric ACP (data not shown).…”
Section: Main Findingssupporting
confidence: 85%
“…Significant changes have been anticipated in communication about end-of-life care following the act. 7 It emphasizes patients to play a central role in ACP. 8 However, having patients directly involved in ACP for end-of-life care is still unusual.…”
Section: Introductionmentioning
confidence: 99%